KINERJA LEMBAGA PERKREDITAN DESA BERBASIS BALANCED SCORECARD SEKECAMATAN BULELENG - Dewanti, Made Amanda; Wiagustini, Luh Putu; Sedana, Ida Bagus Panji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The purpose of this research is know the performance of LPD Buleleng district with Balanced Scorecard Method are evaluated by four perspectives: financial perspectives, customer perspectives, Internal business process perspectives, learning and grow perspectives. In Accordance with the objectives, this research is descriptive research. The Results of this research based on the analysis of the financial perspectives this indicator for performance with healty predicate, the perspectives of costumers is an indicator for a good performance by category, internal process perspective is an indicator for good performance by category and for the last perspective is learning and growth perspective is an indicator for good performance by category. Overall performance LPD showed good performance in the category.
Keywords: Performance, Lembaga Perkreditan Desa, Balanced Scorecard